2020
DOI: 10.1111/bjso.12431
|View full text |Cite
|
Sign up to set email alerts
|

Tweeting about sexism motivates further activism: A social identity perspective

Abstract: Women, more so than men, are using social media activism to respond to sexism. However, when they do, they are also faced with gendered criticisms 'hashtag feminism' that may instead serve to silence them. Based on social identity theory, this research examined how women's social media activism, in response to sexism, may be a first step towards further activism. Two studies used a simulated Twitter paradigm to expose women to sexism and randomly assign them to either tweet in response, or to a no-tweet contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 93 publications
3
10
0
Order By: Relevance
“…Our findings suggest that females demonstrate higher latent and follower engagement SMPP-GI, which confirms previous research that women politically engage in gender issues to enact their gender identity (Chante'Tanksley, 2019 ; Foster et al, 2021 ). Meanwhile, LGBTQ+ individuals report higher latent, follower, and expressive engagement SMPP-GI.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings suggest that females demonstrate higher latent and follower engagement SMPP-GI, which confirms previous research that women politically engage in gender issues to enact their gender identity (Chante'Tanksley, 2019 ; Foster et al, 2021 ). Meanwhile, LGBTQ+ individuals report higher latent, follower, and expressive engagement SMPP-GI.…”
Section: Discussionsupporting
confidence: 90%
“…The dominance of patriarchy and cisheterosexism in society breeds conditions that marginalize women and lesbian, gay, bisexual, trans, queer, and other non-cisheterosexual (LGBTQ+) identifying persons (Cravens, 2020 ; Fitzgerald and Grossman, 2020 ). These conditions can stimulate political participation among members of these oppressed gender categories, which in turn, enhance the group's collective identity, and strengthen the members' sense of personal identity (Vestergren et al, 2017 ; Cravens, 2020 ; Foster et al, 2021 ). Since our present study examines SMPP specific to gender issues, we chose gender as our first explanatory variable of interest.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Yoder et al (2010) on self-labeling found that self-categorization as a feminist predicts engagement in collective action online. Moreover, engaging in Twitter activism in response to sexism was found to promote an enactment of women's social identity, which led to further mobilization for collective action (Foster et al, 2020). Discussing the "Gender digital divide" in developing countries, Antonio and Tuffley (2014) note that one of the most significant benefits of the internet for women is the potential for forming social networks, selfexpression, and a collective identity formation.…”
Section: Online Interactions and Gendermentioning
confidence: 99%
“…In a similar vein, we believe there has been little focus on the outcomes of online protests (but see Foster, 2015;Foster et al, 2021 for some exceptions). As online protest is more accessible for people in repressive contexts (Odağ et al, 2016;Tufekci & Wilson, 2012), it would be worth further investigating what online protest means for protesters and how it may be used to bring about social change yet maintain well-being in a repressive context.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%